1982
DOI: 10.1128/jb.150.1.332-347.1982
|View full text |Cite
|
Sign up to set email alerts
|

Novel peptidoglycans in Caulobacter and Asticcacaulis spp

Abstract: Peptidoglycan sacculi free of poly-beta-hydroxybutyric acid were prepared from whole cells of four species of Caulobacter and two species of Asticcacaluis and from morphological mutants of Caulobacter crescentus and Caulobacter leidyi. Acid hydrolysates of the sacculi were analyzed quantitatively, and each of the hydrolysates was found to contain significant amounts of only five ninhydrin-reactive compounds: alanine, glutamic acid, alpha , omega-diaminopimelic acid, muramic acid, and glucosamine. Four types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 61 publications
(55 reference statements)
1
20
0
1
Order By: Relevance
“…Sacculi from cells in early stages of the cell cycle were uniformly labelled with D-Cys [ Fig. 1B; note that C. crescentus sacculi typically contained granules of polyb-hydroxybutyrate, a storage polymer, which appeared as dark inclusions in EM images (Poindexter and Hagenzieker, 1982)]. During the course of the chase, a significant amount of D-Cys clearing appeared at the centre of the sacculi (Fig.…”
Section: Caulobacter Crescentus Pg Sacculus Elongates From a Central mentioning
confidence: 99%
“…Sacculi from cells in early stages of the cell cycle were uniformly labelled with D-Cys [ Fig. 1B; note that C. crescentus sacculi typically contained granules of polyb-hydroxybutyrate, a storage polymer, which appeared as dark inclusions in EM images (Poindexter and Hagenzieker, 1982)]. During the course of the chase, a significant amount of D-Cys clearing appeared at the centre of the sacculi (Fig.…”
Section: Caulobacter Crescentus Pg Sacculus Elongates From a Central mentioning
confidence: 99%
“…This analysis showed that there were no noticeable differences in the degree of cross-linking or relative abundance of each particular muropeptide species among wild-type, crescentin-null (DcreS and creSHTn5) and crescentin-overproducing strains ( Figure 3D), strongly arguing that curvature is not a product of alterations in peptidoglycan structure. Although this method cannot rule out a structural difference between inner and outer curvature sides that precisely cancels out, it is highly unlikely that the crescentin structure, located at the inner curvature only, (Poindexter and Hagenzieker, 1982), the isolated sacculi contained polyhydroxybutyrate (PHB) granules (arrow). Bar, 1 mm.…”
Section: Crescentin Creates a Gradient Of Peptidoglycan Insertion Ratmentioning
confidence: 99%
“…As FtsZ was found to be required for the cell cycle-regulated burst of polar peptidoglycan synthesis, it may also have a role in stalk biogenesis. C. crescentus stalks contain cross-bands that traverse the width of the stalk (Poindexter and Hagenzieker, 1982) (Fig. 5A and B).…”
Section: Morphogenesis Of the Stalk Requires Two Different Cytoskeletmentioning
confidence: 99%